Peran Kredibilitas Akun Instagram, Persepsi Manfaat, dan Literasi Digital dalam Meningkatkan Kesadaran Gizi Publik - Wiratama, Reva Andrea; Pamungkas, Yoma Bagus; Saptiyono, Ami (LPPM Institut Pendidikan Nusantara Global, 2025)
This study investigates the effect of the National Nutrition Agency's Instagram account credibility on public awareness of the Free Nutritious Meal Program, mediated by perceived usefulness and digital literacy. Employing a quantitative associative causal design, data were collected from 384 Generation Z and millennial Instagram users in Indonesia using purposive sampling. The research instrument was a structured questionnaire with a 6-point Likert scale, and data were analyzed using Generalized Structured Component Analysis (GESCA). Results show that account credibility significantly increases public awareness, with perceived usefulness acting as the main mediator and digital literacy as a borderline mediator. The findings highlight that useful content and audience digital skills are crucial for effective digital health communication. In conclusion, credible government social media, relevant content, and improved digital literacy are essential for enhancing public awareness and participation in strategic health programs.